Antibacterial activity of ethanolic extract of Averrhoa bilimbi L. fruit against Salmonella typhi - Ni Made Riris Divayani Aristyantari; Ni Ketut Ayu Juliasih; Ni Luh Gede Sudaryati; I Nyoman Arsana (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2022)
Averrhoa bilimbi L. fruit has been used in Bali traditional medicine to treat typhoid fever. The fruit contains flavonoids and triterpenoids which are considered to have antibacterial activity. This study aimed to investigate antibacterial activity of ethanolic extract of A. bilimbi L. fruit. The ethanolic extract was prepared by maceration and antibacterial activity was determined by the disc diffusion method against Salmonella typhi cultured on Mueller hinton agar (MHA). Ciprofloxacin was used as positive control and sterile distilled water as negative control. The results showed that the ethanolic extract of A. bilimbi L. fruit at various concentrations of 25; 50; 75 and 100% have an inhibition zone diameter of 0 ± 0; 13.000 ± 1.414; 18.750 ± 1.500 and 20.250 ± 1.707 mm, respectively. In addition, ciprofloxacin at concentration of 1 mg/L has an inhibition zone diameter of 34.250 ± 1.892 mm. In conclusion, the ethanolic extract of A. bilimbi L. fruit has strong antibacterial activity against S. typhi.